(untitled) (Research, Society and Development, 2021)
The voice is present in the processes of human socialization, producing impacts on people’s quality of life, especially those who use the spoken voice in their professional environment, such as teachers. Teaching demands great use of voice and a series of vocal problems among these professionals is verified. This way, this study aims to identify the self-perception of glottal function and the voice handicap index in teachers of public schools in Marabá-PA. This research is a transversal, prospective and quantitative study, with a descriptive approach through the application of two validated questionnaires: Glottal Function Index (GFI) and Voice Handicap Index (VHI), in 78 public school teachers of the city. The variables analyzed were: gender, age, teaching time and daily workload. The chi-squared test was performed with a significance level of p<0,05 using Microsoft Excel 2010. In this study, the female gender predominated (54%), with the highest number of people in the age group 31 to 40 years (44%), showing an overall mean score of 8.04 for VHI-10 and 6.45 for GFI, with a statistically significant association between VHI-10 and GFI (p<0,01). Therefore, the study points out the need for greater attention regarding voice self-perception, which suggests the implementation of new diagnostic tools that confirm possible vocal disorders, thus contributing to the maintenance of vocal health and teacher’s quality of life.